(untitled) (Medical Forum Monthly, 2021)
Objective: To determine the effects of sub-occipital myofascial release in patients with cervicogenic headache. Study Design: Randomized Clinical Trial study Place and Duration of Study: This study was conducted at the conducted at Lateef Clinic Nespack society and Al-Kareem Aman Health Care Center, Lahore from July 2020 to February 2021. Materials and Methods: Non-probability convenient sampling technique was used, 22 patients were included and were randomized through sealed envelope method in two groups. Group A was given sub-occipital myofascial release along with conventional therapy while group B was given cervical mobilization and conventional therapy. Participants of both gender with age range 20 to 50 years with Neck pain referring the unilateral pain to the sub-occipital region and head were included in the study. Patient who do not tolerate the cranio-cervical Flexion rotation test were excluded from the study. Neck Disability Index, Pain Numerical Rating Scale, and goniometer were outcome measuring tools. The data was analyzed using SPSS 21. Results: The descriptive statistics regarding age in myofascial release showed that mean and standard deviation found to be 30.63±4.90 while age in control group found to be that of 33.18±3.62. NDI of Group A pre-treatment 21.72 ± 2.8 and post treatment 6.27 ± 1.8. Group B 23.09 ± 4.4 and post treatment 11.00 ± 3.3 and P value was less than 0.05. PNRS showed same result with significant p-value. Cervical ranges were also improved more in Group A. Conclusion: The study concluded that both Sub-occipital myofascial release and cervical mobilization were effective in reducing pain of cervicogenic headache. The results were statistically significant for both groups, though the sub-occipital myofascial release group found better than conservative group in terms of mentioned outcome measures on the basis of mean differences.